Highly‐tunable and wide stopband microstrip bandpass filters. Issue 5 (20th February 2021) - Iqbal, Amjad; Smida, Amor; Waly, Mohamed I; Mallat, Nazih Khaddaj
Abstract: This paper presents the design of a highly‐tunable single‐ended and balanced filter with improved upper stopband performance. The proposed filters are designed using a spurline and a U‐shaped stepped impedance resonator (SIR) with a varactor diode connected to the open‐circuited end. A spurline is introduced in both designs to achieve wide stopband performance by suppressing the higher‐order modes. The proposed filters have high tunable ranges (single‐ended: 2.35‐3.99 GHz; balanced: 2.39‐4 GHz), low insertion losses (IL) (single‐ended: 0.07‐0.2 dB; balanced: 0.21 to 1.1 dB) and wide upper stopband performance (single‐ended: 3.79 f 1 with a rejection level higher than 20 dB; balanced: 3.79 f 1 with a rejection level higher than 20 dB). Performance of both filters are experimentally validated by comparing the experimental results with the simulated ones. Both filters can cover most of the fifth‐generation (5G) wireless communication bands with different biasing voltages (capacitance). When both filters are compared with state‐of‐the‐art filters, the proposed filters are found to achieve high tunable ranges with low IL and wide upper stopband performance.